Efektivitas Model Konseling Kelompok Berbasis Nilai-Nilai Pesantren untuk Meningkatkan Pengaturan Diri Santri di Pesantren Kalimantan Timur (Jurnal Bimbingan dan Konseling Islam, 2019)
The objective of this study were: test the the effectiveness of the group counseling model based on pesantren’s values to improve students’ self-regulation. This research is a field research (field research) using an experimental research design. The variable of this study consisted of independent variables, namely the group counseling model based on pesantren values ??and the dependent variable namely self-regulation. The population in this study were class VIII students of Madrasah Tsanawiyah (MTs) levels from Al-Mujahidin Islamic Boarding School in Samarinda City, Ihya Ulumuddin Islamic Boarding School in Samarinda City and Al-Ihsan Tanah Grogot Islamic Boarding School-Paser Regency, all of which are located in East Kalimantan Province. In each pesantren the research location was chosen for each of the 3 classes to measure the level of self-regulation by using the self-regulation scale as a form of pretest (initial evaluation). Furthermore, with a purposive sampling method a sample of 8-10 santri with the lowest scores were either in the very low, low or moderate self-regulation category of each pesantren to be subjected or to become group members who would receive treatment in the form of value-based group counseling models boarding school values ??at the empirical / field test stage. Data collection techniques consist of the use of a psychological scale (self-regulation), observation, and documentation study. Data analysis techniques to test the effectiveness of group counseling models based on pesantren values ??to improve self-regulation of students using pre-experimental designs: one group pretest-posttest. Test the hypothesis using the Paired Sample T-Test.